Unimodality Problems of Multinomial Coefficients and Symmetric Functions - Su, Xun-Tuan; Wang, Yi; Yeh, Yeong-Nan (The Electronic Journal of Combinatorics, 2011)
In this note we consider unimodality problems of sequences of multinomial coefficients and symmetric functions. The results presented here generalize our early results for binomial coefficients. We also give an answer to a question of Sagan about strong q-log-concavity of certain sequences of symmetric functions, which can unify many known results for q-binomial coefficients and q-Stirling numbers of two kinds.